The Impact of Digital Economy and Net Export of Goods and Services Towards Employment in the Selected Southeast Asia Countries - Ngah Mohamad, Muhamad Nazrin Farhan; Ma’in, Masturah; Mohamad Azhar, Nur Azirah Zahida; Susamto, Akhmad Akbar (Information Management and Business Review, 2024)
The digital economy is rapidly growing and transforming the way people work and do business globally. This growth has a significant impact on employment in the Association of Southeast Asian Nations (ASEAN) countries. This study aimed to examine the impact of the digital economy and net export on employment in selected ASEAN members, Malaysia, Indonesia, Singapore, and Thailand. Sample years were extracted from 1991 to 2021 and the panel data regression method was applied in this study. The result of this study showed that the digital economy; fixed broadband subscription (LBROAD), internet users (LUSER), and net export (LEXP01) had a significant influence on employment (LTEMP).